Protective effects of vitamin E against hypercholesterolemia-induced age-related diseases - YILMAZ, BETÜL; KARTAL ÖZER, NESRİN (BMC, 2012)
Hypercholesterolemia is a major risk factor for age-related diseases such as atherosclerosis and Alzheimer's disease (AD). Changes in human plasma cholesterol levels results from the interaction between multiple genetic and environmental factors. The accumulation of excess cholesterol in blood vessels leads to atherosclerosis. Many studies on this field show that differential expression of oxidative stress-related proteins, lipid metabolism-related enzymes, and receptors response to atherogenic diet. Additionally, excess brain cholesterol has been associated with increased formation and deposition of amyloid-beta peptide from amyloid precursor protein which may contribute to the risk and pathogenesis of AD. To consider genetically, more than 50 genes have been reported to influence the risk of late-onset AD. Some of these genes might be also important in cholesterol metabolism and transport. Epidemiological studies have shown an association between high intake and high serum concentrations of antioxidant vitamins like vitamin E and lower rates of ischemic heart diseases. It has been known that vitamin E also inhibits smooth muscle cell proliferation by non-antioxidant mechanism. On the basis of the previous results, vitamin E has been accepted as an important protective factor against hypercholesterolemia-induced age-related diseases.
Keywords: Alzheimer's disease; Atherosclerosis; Hypercholesterolemia; Vitamin E; Tocotrienol; PROTEIN-KINASE-C; INCREASED OXIDATIVE DAMAGE; SCAVENGER RECEPTOR EXPRESSION; DIETARY ANTIOXIDANT VITAMINS; CORONARY-HEART-DISEASE; RICH FRACTION TRF25; ALPHA-TOCOPHEROL; ALZHEIMERS-DISEASE; LIPID-PEROXIDATION; OXIDIZED LDL